Overview of control techniques for multicellular converter - P. Djondiné (Журнал інженерних наук)
The structure multicellular converters, which appeared at the beginning of the 1990s, makes it possible to share the constraints in tension and it also improves the harmonic contents of the wave forms. To benefit as well as possible from the large potential of the multicellular structure, an appropriate distribution of the voltages crossing each cell is needed. These converters are drastically used in industry as well as in research. One of the main limitations of these converters is unregulated supply of voltage and current. To overcome these problems there are various control techniques used in combination with these converters. In this review we summarized few of these control techniques. Some well known control techniques are PID, sliding mode control and Petri nets control. We have also paid attention on the advantages and disadvantages of these techniques with basic operating principle.